Optimising Digital Marketing Using Marketplaces to Increase Onion Sales at Wale Warehouse - Pangaribuan, Muhammad Alfin; Harahap, Baginda; Siregar, Muhammad Furqon (PT. Technology Laboratories Indonesia (TechnoLabs), 2026)
This study aims to analyse and describe the digital marketing optimisation strategies implemented by Gudang Wale to increase onion sales through the Facebook marketplace. This study also identifies effective digital marketing strategies and reveals the obstacles faced in implementing digital marketing in this marketplace. The approach used is descriptive qualitative with data collection techniques through in-depth interviews with 8 informants consisting of the owner of Gudang Wale, senior management, IT staff, digital marketing staff, operational staff, and regular consumers. Informants were determined using purposive sampling techniques. The results show that the digital marketing optimisation strategy is not yet fully effective, with the main obstacles including limited technological knowledge, inadequate IT infrastructure, and unattractive product displays. Although the use of the Facebook marketplace influences consumer behaviour, fierce competition and difficulty in finding products are challenges for consumers. Barriers to digital marketing optimisation impact the effectiveness of sales growth. Therefore, Gudang Wale needs to improve its digital strategy by utilising more advanced technology and enhancing the appeal of its content on the Facebook marketplace to overcome existing barriers and significantly increase onion sales.